Material Selection and Fluid Flow Analysis of Parallel Flow Heat Exchanger - , Christian Emeka Okafor; , Alex Dubem Tagbo; , Obiora Jeremiah Obiafudo; , Emmanuel Chinagorom Nwadike (Archives of Current Research International, 2017)
Aims: To select appropriate material and undertake fluid flow analysis of parallel flow heat exchanger. Methodology: Dynamic simulation study was performed to evaluate conditions of heat transfer of water through heat exchanger using ASPEN HYSYS. Cambridge Education Selector (CES) Granta software was used to select the suitable candidate materials for the heat exchanger. The properties of the selected materials and fluid characteristics were implemented in Computational Fluid Dynamics (CFD) to solve and analyze the fluid flow. Results: For inner pipe, low alloy steel having maximum thermal conductivity of 55(W/m°C) and specific heat capacity of 530 (J/kg°C) respectively was selected and used. For the outer pipe, cast iron, gray having thermal conductivity of 72 (W/m°C) and specific heat capacity of 495(J/kg°C) passed the selection criteria and was used.The total heat transfer surface area and hydraulic diameter was determined as 0.1341634m2and 0.481m respectively while the velocity of flow (V) for hot and cold fluid was established as 0.00014518 m/sec and 0.000196817 m/sec respectively. Conclusion: The material-process decision on a parallel flow heat exchanger design was reduced to trade-off between performance and cost. The data obtained from the experimental record are well matched with computational fluid dynamics simulated values at different mass flow rate.